A Theological Review of Hope in Suffering Based on Lamentations 3:21-33 - Panggabean, Kristina (Sekolah Tinggi Teologi Trinity Parapat, 2023)
Why do suffering Christians often feel frustrated? They seem don't see God's help, or lose hope. How should a Christian deal with suffering? This research aims to answer these questions. Using the Bible, commentaries, and related research articles, the author carries out an exegesis of Lamentations 3:21-33. Through this research it was found that the Prophet Jeremiah expressed his concern for the suffering experienced by the people of Judah. However, through that suffering, God's truth was revealed. In the midst of the suffering experienced by his people, Jeremiah had confidence in God's never-ending care, faithful love and mercy. The prophet believed and relied on Allah to provide for his needs in the midst of suffering. This hope in suffering gives strength to people experiencing suffering today, especially Christians.